IOS 10 programming for beginners : begin your iOS mobile application development journey with this accessible, practical guide - Clayton, Craig (Packt Publishing, 2016)
Begin your iOS mobile application development journey with this accessible, practical guide About This Book Use Swift 3 and latest iOS 10 features to build awesome apps for iPhone and iPad Explore and use a wide range of Apple development tools to become a confident iOS developer From prototype to App Store--find out how to build an app from start to finish! Who This Book Is For This book is for beginners who want to be able to create iOS applications. If you have some programming experience, this book is a great way to get a full understanding of how to create an iOS application from scratch and submit it to the App Store. You do not need any knowledge of Swift or any prior programming experience. What You Will Learn Get to grips with Swift 3 and Xcode, the building blocks of Apple development Get to know the fundamentals of Swift, including variables, constants, and control flow Discover the distinctive design principles that define the iOS user experience See how to prototype your app with Swift's Playgrounds feature Build a responsive UI that looks great on a range of devices Find out how to use CoreLocation to add location services to your app Add push notifications to your app Make your app able to be used on both iPhone and iPad In Detail You want to build iOS applications for iPhone and iPad--but where do you start? Forget sifting through tutorials and blog posts, this is a direct route into iOS development, taking you through the basics and showing you how to put the principles into practice. With every update, iOS has become more and more developer-friendly, so take advantage of it and begin building applications that might just take the App Store by storm! Whether you're an experienced programmer or a complete novice, this book guides you through every facet of iOS development. From Xcode and Swift--the building blocks of modern Apple development--and Playgrounds for beginners, one of the most popular features of the iOS development experience, you'll quickly gain a solid foundation to begin venturing deeper into your development journey. For the experienced programmer, jump right in and learn the latest iOS 10 features. You'll also learn the core elements of iOS design, from tables to tab bars, as well as more advanced topics such as gestures and animations that can give your app the edge. Find out how to manage databases, as well as integrating standard elements such as photos, GPS into your app. With further guidance on beta testing ...